2020
DOI: 10.1111/jpc.14825
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal predictors of intestinal pathologies in fetal bowel dilatation

Abstract: AimFetal bowel dilatation (FBD) in the late trimester of pregnancy can be related with varies of prognosis. Our aims were to obtain antenatal factors that might have relevance for the distinct prognosis with FBD.MethodsSeven features of 68 pregnancies presented with FBD were assessed. The best cut‐off value to predict intestinal outcomes was selected using receiver‐operating characteristics curves, and the effective variables were included into a logistic regression model.ResultsThe best cut‐off valves to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 9 publications
4
18
0
Order By: Relevance
“…In some cases and with experienced ultrasound technicians, it is possible to observe fetal gastric dilation. In cases of type I stenosis or atresia, the amniotic fluid may be within normal limits and the symptoms may start later, as in the case reported [ 2 ] herein.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In some cases and with experienced ultrasound technicians, it is possible to observe fetal gastric dilation. In cases of type I stenosis or atresia, the amniotic fluid may be within normal limits and the symptoms may start later, as in the case reported [ 2 ] herein.…”
Section: Discussionsupporting
confidence: 50%
“…Despite the aggressiveness described, all the reported cases presented survival after the complete resection of the lesion. In one of the selected cases, where there was a diffused involvement of the gastrointestinal tract, the use of vincristine and propranolol associated with surgical treatment caused the remission of the symptoms of anemia and abdominal pain [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…described 68 cases with prenatal diagnosis of fetal bowel dilatation. They found that the congenital gastrointestinal tract anomalies included 24 cases (92.3%) of intestinal atresia, one case (3.85%) of small intestine volvulus and one case (3.85%) of malrotation [ 11 ]. In the case we presented, there was only fetal bowel dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal volvulus without malrotation is one of the differential diagnoses of fetal intestinal dilatation [1] . This is an extremely rare condition known to cause abdominal compartment syndrome in newborns [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%